Guidelines for Programs and Departments in Undergraduate Medical Technology Sciences - Elmansorry E* and El khoga J, (AlQalam Journal of Medical and Applied Sciences, 2017)
The Faculty of Medical Technology at Tripoli University is the oldest undergraduate medical school in Tripoli, it was established in 1986, as a higher institute in the fields of Medical Laboratory, Nursing and Pharmaceutical Technology. The Bachelor degree of Medical Technology was introduced in 1996, profession for health science-based academic qualification in the various laboratory technology disciplines, especially in the fields of Medical Laboratory, Dental Technology, Intensive care & Anaesthesia, Pathology and Public Health. The purpose of this paper is to give faculty readers an overview of educational and study activities, including development in study plans, training, research methods for preparing the students for their future career of undergraduate medical technology education in Tripoli University. We made a general survey of the different departments in the faculty to demonstrate an in depth knowledge of their activities so that we focused on the educational and research methods at the faculty. We analysed the development in theory and clinical modules, research and clinical training programs in the different fields. We found despite the great improvement in the learning methods, increasing the numbers of the qualified teaching staff, but the faculty has to cooperate with the international scientific community to develop the teaching and research activities.